Cos’è ritratto per Leonardo? Una esercitazione paziente intorno a un probabile disegno autografo (Materiali di Estetica. Terza serie, 2020)
A lost and rediscovered drawing by Leonardo da Vinci, what does it inspire? What circumstantial investments does it imply to be recognized? In a nutshell, this is the dispute: the recovery and identification of a graphic artifact referable in the first instance to Leonardo’s school, and, in the second instance to Leonardo da Vinci himself.
Keywords: Leonardo’s Rediscovered Drawing; Graphic Artifact; Leonardo’s School